REFORM OF HOUSING AND COMMUNAL SERVICES IN RUSSIA: ANALYSIS AND EVALUATION OF THE EFFECTIVNESS - A. Kh. Kazanbieva (Вестник университета)
The results of state reforms in the sphere of housing and communal services have been summarized and analyzed in the article. The importance of housing and communal services as a branch of the economy has been substantiated. The state of housing and communal services has been investigated and an assessment of the effectiveness of reforms in this area has been given. The characteristics of the main measures and projects on modernization of housing and communal services has been given. Based on the analysis of statistical indicators, the trends in the development of the industry have been designated. The conclusion about the effectiveness of the reforms of housing and communal services has been made.